Modulatory effect of dietary probiotic and prebiotic supplementation on growth, immuno-biochemical alterations, DNA damage, and pathological changes in E. coli-infected broiler chicks - Hashem, Mohamed A.; Hassan, Azza E. A.; Abou-Elnaga, Hala M. M.; Abdo, Walied; Dahran, Naief; Alghamdi, Ali H.; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2022)
Avian pathogenic Escherichia coli is one of the principal causes of heavy economic losses to the poultry industry. Little is known about the underlying mechanisms, particularly the potential role of immunoglobulin A and the DNA damage, involving the beneficial effects of dietary supplementation of probiotic and prebiotics in avian collibacillosis. The current study investigated the probiotic and prebiotic dietary supplementation potential effects on E. coli-infected broiler chicks. A total of 120 1 day old unsexed Hubbard chicks were divided into six groups: Group 1 was considered as a negative control; Group 2 was supplemented with 1 g/kg feed of Lactobacillus plantarum; Group 3 was supplemented with amylase enzyme; Group 4 served as a positive control infected orally by E. coli O78; Group 5 was supplemented with Lactobacillus plantarum from 1 day old, and then infected orally with E. coli O78; and Group 6 was supplemented with amylase enzyme from 1 day old and then infected orally with E. coli O78. For all examined groups, the experimental period lasted for 42 days. The E. coli-infected group revealed a decrease in body performance parameters, with a significant increase in liver enzymes and renal function tests. The same group recorded a significant decrease of serum total proteins, albumin and globulins, alteration of immunological parameters, antioxidant enzymes, oxidative stress parameters, and comet assay revealed highly damaged DNA in the liver and intestine. Under histopathological examination, a series of histopathological changes in liver, kidney, and intestine were observed. The infected chick pretreated with probiotic or prebiotic demonstrated an improvement of body performance parameters besides a significant decrease in the hepatic enzymes and renal function tests. We noticed that in treated groups there was a significant increase of serum total proteins of serum albumin and globulin level, and the immunological parameters and antioxidant enzymes. Furthermore, DNA damage and histopathological changes within hepatic, renal and intestinal tissues were markedly diminished in treated groups compared with infected group. In conclusion, the adverse effects of E. coli could be modulated through chemoprevention administration of probiotic and prebiotic.